Analisis Pendapatan Perempuan Pesisir dalam Meningkatkan Pendapatan Pengrajin Usaha Cocopot di Desa Lambangi Kecamatan Kolono Timur Kabupaten Konawe Selatan - Nur Adzy Mahdalena; Hartina Batoa; Yoenita Jayadisastra (Fakultas Pertanian Universitas Halu Oleo, 2022)
This studied aim to determined the income of coastal women through Cocopot business craftsmen in Lambangi Village, East Kolono District, South Konawe Regency. Research has been conducted on a group of coastal women who are developing a Cocopot business. The time of the research was carried out in March 2022 with a total of 26 respondents who were members of 4 groups, each group consisting of 6 and 7 members. Research variables measured in this study are reception, production costs and operating revenues. Analysis of the data used to determine the amount of income is to use the income calculation formula. The results showed that the amount of income earned per month from the production of Cocopot handicrafts for all groups of women in Lambangi Village, East Kolono District, South Konawe Regency was Rp. 3,551,000. The amount of income obtained can increase income, where waste that was not used is then processed into a product that has economic value.